Subcutaneous allergen-specific immunotherapy with Gramineae pollen in children with allergic rhinoconjunctivitis - Yilmaz, Ercan; Topal, Erdem; Ertoy Karagol, Hacer Ilbilge; Ozbey, Mehmet Yavuz; Cavkaytar, Ozlem; Arga, Mustafa (Annals of Medical Research, 2023)
Aim: Patients experiencing persistent complaints of moderate-severe allergic rhinoconjunctivitis despite symptomatic treatment are considered candidates for Allergen Specific Immunotherapy (ASIT). The present study aims to assess the effectiveness and safety of ASIT using Gramineae pollen in children afflicted by allergic rhinoconjunctivitis. Materials and Methods: The study involved participants between 5 and 18 years of age who had allergic rhinoconjunctivitis. These participants were divided into two distinct groups. The initial group underwent ASIT, while the other constituted the control group that refrained from it. The control group comprised participants with akin ages and equivalent disease durations. Visual analog scores (VAS), daily symptom scores (dSS), daily medication scores (dMS), and combined symptom and medication scores (CSMS) were assessed at three specific time junctures: Baseline, post the initial year of ASIT, and after the second year of ASIT. Results: The study encompassed 188 children who had been diagnosed with allergic rhinoconjunctivitis. Among these, 94 patients had undergone immunotherapy. Of the total cases, 105 (55.9%) were male, with a median age of 14 years (range: 7-18 years). Among the patients who had received ASIT, there were statistically significant reductions in VAS, dSS, dMS, and CSMS after one and two years of therapy when compared to the baseline values (p<0.001). Upon comparing the group receiving ASIT with the control group after a two-year follow-up, notable reductions were observed in VAS, dSS, dMS, and CSMS (p<0.001). Five patients (5.3%) experienced systemic reactions. Conclusion: The current study demonstrated that ASIT with Gramineae pollen is clinically effective in patients with Graminae pollen-induced allergic rhinoconjunctivitis.